(untitled) (Malaysian Journal of Civil Engineering, 2018)
The paper develops an automated assessment tool specially tailored for corroding steel pipeline used to convey hydrocarbon deposit. The proposed tool named PICA integrates deterministic and reliability method to evaluate the time-variant remaining allowable pressure of steel pipelines subjects to internal and external corrosion based on series of metal loss data. The deterministic assessment method is preferred by pipeline operator due to its simplicity, yet the accuracy is still arguable as the integrity of assessment results is dominantly governed by inherent uncertainties which insufficiently covered even by the introduction of safety factor. Whereas reliability assessment requires systematic data sampling and matching method as well as probabilistic nature of the parameters to give more credible and accurate result especially in estimating the corrosion growth rate. The combination of data sampling, data analysis, structure assessment and integrity prediction both in the form of deterministic and reliability-based methodology has great potential to be developed as robust and potent software. This assessment software covers wide range of options including selection of assessment codes, corrosion models, data sampling techniques, assessment methods and particularly effective to manage the vast amounts of collected data relating to pipeline condition, in a way that enables pipeline operators to monitor the pipeline integrity efficiently. By integrating various stages of pipeline assessment procedure into a unified systematic assessment framework, it can greatly assist pipeline operator to protect the public, financial investment and environment from such devastating effects owing to pipeline failures.